Pengaruh Capital Intensity, Inventory Intensity, Profitabilitas dan Leverage Terhadap Agresivitas Pajak - Hidayat, Agus Taufik; Fitria, Eta Febrina (STIE PGRI Dewantara Jombang, 2018)
This research aims to examine the effect of capital intensity, inventory intensity, profitability and leverage on the tax aggressiveness of manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange in the period 2013-2017. Profitability is proxied using the formula Retrun On Assets (ROA), proxy leverage using the formula Debt to Total Assets Ratio (DAR) and tax aggressiveness is proxied using Effective Tax Rate (ETR). The type of research used is quantitative. The population in this study is a consumer goods manufacturing sector listed on the Indonesia Stock Exchange in the period 2013-2017 consisting of 42 companies with a total population of 132 populations. Determination of samples using purposive sampling method with a total sample of 40 samples from 8 selected companies. The results of the study show that capital intensity and leverage affect the tax aggressiveness. While Inventory intensity and profitability do not affect tax aggressiveness.Â